Information access preferences and behaviour of Blind Foundation Library clients. (March 2019) - Calvert, Philip; Creaser, Claire; Pigott, Chris
Library services to blind and visually impaired readers are changing as computer technology makes it possible to deliver reading material in a variety of new media formats. The Blind Foundation of New Zealand surveyed its library clients to discover the reading formats they currently used and which ones they preferred. The survey also asked questions about their access to computer technology and their personal assessment of their technological competency. There was a particular focus in the survey on the DAISY format and on services offering books by download. Analysis of the survey data shows that access to computer technology roughly matches the national profile. Use of computers generally declines with age, with iPhones and iPads being the exception. The DAISY format is both the most used and the most preferred format for reading, though not so overwhelmingly as to suggest other formats can be dropped. Computer competency declines with age, but among the younger respondents there seemed to be both the ability and the confidence to download books, and some were already using that service provided by the library. The library will make further investigations into why relatively few clients currently use the download service, and how clients envisage using such a service in the future.